Reliability of 10-meter sprint tests, spider run beach test and anaerobic capacity of beach tennis players - Bravin, Leonardo F.; Sagrillo, Lorenzo G.; Machado, Alexandre Fernandes; Reis, Carlos Henrique; Paiva, Rodrigo; Miranda, Joao Marcelo [UNESP]; Rica, Roberta L.; Bocalini, Danilo S. (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2024)
The objective of this study was to evaluate the reliability of the 10-meter sprint, spider run and anaerobic capacity tests, both protocols were adapted for beach tennis. Material and methods: 27 healthy adults of both sexes who were physically independent and practiced beach tennis participated in the experiment. 3 visits were carried out, the 1st visit to the laboratory for anthropometric assessment and the 2nd and 3rd visits to the beach tennis court, to carry out adapted tests: 10 meter sprint, spider run and anaerobic capacity. Results: No significant differences (p > 0.05) were found between the 1st and 2nd assessments in all tests. The 10m sprint test and spider run beach test showed a low effect size (g = 0.11). The reliability between the measurements of the 10-meter sprint tests presented values corresponding to-0.02 +/- 0.20 BIAS (-0.42-0.38) and-0.08 +/- 1.58 BIAS (-3.02-3.19) for the spider run beach test. In the anaerobic test, 0.20 +/- 0.78 BIAS (-1.33 -1.74) for Tm (average time), 0.11 +/- 0.33 BIAS (-0.53 -0.75) for Tmin (minimum time) and 0.18 +/- 0.59 BIAS (-0.98 -1.34) for Tmax (maximum time) respectively. Conclusion: The 10-meter sprint test, spider run beach test and anaerobic capacity test adapted for beach tennis showed adequate reliability in the values, and these tests can be used in training programs for athletes in this modality.
Keywords: Physical Education and Training; Racquet Sports; Athletic Performance; health promotions; return to sport